2014
DOI: 10.3889/oamjms.2014.020
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter Pylori Infection in Children with Type 1 Diabetes Mellitus

Abstract: Objective: To evaluate H. pylori infection and virulent strain in diabetic children. Patients:In this study 53 type 1 diabetics and 53 of normal volunteers were included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The possible reasons for the disparity observed in the prevalence of infection include differences in study populations in terms of age and sample size. Age should be considered as a factor affecting H. pylori infection, as the exposure to H. pylori organisms increases with age [8,14], and it is imperative to compare similar age groups when studying the Based on the results of some studies, many factors can influence the prevalence of H. pylori infection among children with Diabetes, such as age, age at the onset of diabetes, duration of diabetes, BMI, FPG and HbA 1 c1 [10,16]. In one study, Feyad et al Found that children with diabetes and positive H. pylori infection comorbidity are older, have had an earlier onset of diabetes, have a larger BMI and a higher HbA 1 c compared to the negative infected group [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible reasons for the disparity observed in the prevalence of infection include differences in study populations in terms of age and sample size. Age should be considered as a factor affecting H. pylori infection, as the exposure to H. pylori organisms increases with age [8,14], and it is imperative to compare similar age groups when studying the Based on the results of some studies, many factors can influence the prevalence of H. pylori infection among children with Diabetes, such as age, age at the onset of diabetes, duration of diabetes, BMI, FPG and HbA 1 c1 [10,16]. In one study, Feyad et al Found that children with diabetes and positive H. pylori infection comorbidity are older, have had an earlier onset of diabetes, have a larger BMI and a higher HbA 1 c compared to the negative infected group [10].…”
Section: Discussionmentioning
confidence: 99%
“…The link between T1DM and H. pylori still remains controversial. Some studies have suggested that the high prevalence of this infection in patients with T1DM [10][11][12][13][14] is related to the duration of diabetes, dyspepsia, age, sex, BMI, blood pressure, fasting plasma glucose (FPG) and Hemoglobin A1c (HbA 1 c) level [10,11]. H. pylori infection can lead to hyperglycemia in children with Diabetes Mellitus, and its mechanisms are unknown but are thought to include the secretion of counterregulatory hormones due to stress in addition to the production of cytokines.…”
Section: Introductionmentioning
confidence: 99%